Computer Simulation of Biological Processes at the High School (Pedagogy of Higher and Secondary Education, 2018)
Komarova O. V. and Azaryan A. A. Computer Simulation of Biological Processes at the High School.Research goals: the necessity of study in high school of the law of Hardy — Weinberg as one of the fundamental genetic laws was justified. The peculiarities of using the method of model experiment in the studyof the genetic and evolutionary processes in populations with the use of computer technology. Object of research: computer simulation of population genetic structure. Subject of research: computer simulation of genetic and evolutionary processes in ideal and real populations. Research methods: pedagogical experiment (survey), analysis of scientific publications on the use of the high school method of modelling genetic and evolutionary processes in populations, computer simulation. Results of the research: a web page for processing by the pupils of the modelling results of genetic and evolutionary processes in populations was created.
Keywords: modelling; computer simulation; ideal population; the law of Hardy — Weinberg; statistical methods; evolution factor; natural selection; genetic structure of population; microevolution; diagram; graphs; the law of large numbers